Eating Behaviors in Relation to Child Weight Status and Maternal Education - Priscilla Ayine; Vaithinathan Selvaraju; Chandra M. K. Venkatapoorna; Yida Bao; Philippe Gaillard; Thangiah Geetha (MDPI AG, 2021)
Background: The eating behavior of children is important to maintain a healthy weight. This current study explored the differences in children's eating behaviors and their relation to weight status and maternal education level, using the child eating behavior questionnaire (CEBQ). Methods: The study recruited 169 participants aged between six and ten years. Multinomial logistic regression was conducted to examine the association between the CEBQ factors and children's body weight status. The association between the CEBQ scores and maternal educational levels was examined using a one-way analysis of variance (ANOVA). Results: The multinomial logistic regression findings indicate that children in the obese group exhibited a significant increase in food responsiveness, enjoyment of food, emotional overeating, and a decrease in satiety responsiveness compared to normal weight children. The one-way ANOVA showed a significant difference in subscales under the food approach (food responsiveness, desire to drink, emotional overeating) and food avoidance (satiety responsiveness) based upon the child's weight status. The three subscales under the food approach category were significantly dependent upon the maternal education but did not have a significant association with food avoidance. Conclusions: The results suggest that the increase in food responsiveness and emotional overeating in obese children is influenced by maternal education.